Navigating political terrain: a comprehensive review of leadership theories in political science - Pohan, Ibnu Asqori; Ismail, Muhamad Takiyuddin; Syed Annuar, Sharifah Nursyahidah (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
Political science is increasingly focusing on the study of leadership factors in its field scope. Therefore, the primary objective of this article is to systematically analyze the use of leadership theories in scholarly publications of political science. This paper also underscores the lack of leadership theories or concepts in political science, offering insights to anyone interested in examining leadership in this academic discipline. This study introduces an alternative framework for analyzing leadership, specifically emphasizing political leadership. Thus, the question addressed in this study is: What leadership theories are applied to the study of political science? This study utilizes the systematic literature review approach, except for the Appraisal Quality stage, to examine political leadership theory and the notion of utilization as discussed in political science. The ROSE protocol is employed in this study due to its suitability for mapping and qualitative studies. Furthermore, PICo is used to formulate research questions in the context of this study. The results of this study, which involved the review of 75 papers, revealed the implementation of leadership theories and concepts in 15 distinct contexts or focus areas. The analysis of leadership in political science places significant emphasis on the dimensions of transformative and transactional leadership styles. Both leadership styles are frequently used in various research contexts. Overall, the prevalence of transformative and transactional leadership theories in political science can be understood as a reflection of the constraints political scientists face in comprehending the nature of leadership within a political context from a scientific standpoint.